2009
DOI: 10.1002/mrm.22050
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of human peripheral nerve stimulation thresholds in a 3‐axis planar gradient system

Abstract: In MRI, strong, rapidly switched gradient fields are desirable because they can be used to reduce imaging time, obtain images with better resolution, or improve image signal-to-noise ratios. Improvements in gradient strength can be made by either increasing the gradient amplifier strength or by enhancing gradient efficiency. Unfortunately, many MRI pulse sequences, in combination with high-performance amplifiers and existing gradient hardware, can cause peripheral nerve stimulation (PNS). This makes improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The achievable slew rates for the coils are ∼10 times higher than typical whole‐body coils. Previous work done by Feldman et al (14) has shown that planar coils are able to operate at significantly higher slew rates than conventional cylindrical systems without causing PNS, demonstrating that the relationship between PNS and slew rate is complicated and geometry dependent. This observation was the motivation for this study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The achievable slew rates for the coils are ∼10 times higher than typical whole‐body coils. Previous work done by Feldman et al (14) has shown that planar coils are able to operate at significantly higher slew rates than conventional cylindrical systems without causing PNS, demonstrating that the relationship between PNS and slew rate is complicated and geometry dependent. This observation was the motivation for this study.…”
Section: Discussionmentioning
confidence: 96%
“…The size constraint imposed by the scanner bore, along with the necessity of maintaining access for the subject has required that the design of these coils stray from traditional cylindrical geometry (6, 9–13). Because of their open geometry and PNS advantages (14), planar gradient insert coils have been used as additional insert coils exclusively for high‐performance diffusion‐weighted imaging (1). Challenges in planar gradient coil design include relatively poor gradient homogeneity, torque issues, asymmetric eddy‐current profiles, and a drastic decrease in efficiency as the region of interest (ROI) moves away from the coil surface.…”
Section: Introductionmentioning
confidence: 99%
“…The fast switching gradient fields are applied for spatial encoding of the MRI signal and can cause peripheral nerve stimulation and implant heating. They are also responsible for the noise in the MRI scanner room, which can reach levels of 100 dB or more and potentially lead to hearing damages [74,119–121,118,122126,30,31,127,128,16,90,129,37,130133,57,58,134,135,69]. …”
Section: Magnetic Fields In An Mri Suitementioning
confidence: 99%
“…There are multiple factors influencing the interactions of gradient fields with biological tissues and they depend on the frequency of the gradient field, the maximum and average flux densities, the presence of harmonic frequencies, the waveform characteristics of the signal, the polarity of the signal, the current distribution in the body, the electrical properties, and the sensitivity of the cell membrane [119–121,118,126,31,128,37,131,133,63,134]. The acoustic noise during an MRI exam is also caused by the gradient system [121,118].…”
Section: Peripheral Nerve Stimulation and Hearing Damage Caused By Thmentioning
confidence: 99%
“…Pulse sequences with high slew rates run the risk of inducing peripheral nerve stimulation (9). Some localized and noncylindrical gradients have been shown to have higher stimulation thresholds (10, 11) and permit rapidly switched gradient fields to be operated with larger gradient magnitudes. The obvious challenge is that restricting the field of view results in artifacts (12).…”
mentioning
confidence: 99%